Migration and dynamics: How a leakage of human capital lubricates the engine of economic growth - Gerhard Sorger; Oded Stark; Yong Wang (University of Tübingen, Faculty of Economics and Social Sciences, 2013)
This paper studies the growth dynamics of a developing country under migration. Assuming that human capital formation is subject to a strong enough, positive intertemporal externality, the prospect of migration will increase growth in the home country in the long run. If the external effect is less strong, there exists at least a level effect on the stock of human capital in the home country. In either case, the home country experiences a welfare gain, provided that migration is sufficiently restrictive. These results, obtained in a dynamic general equilibrium setting, extend and strengthen the results of Stark and Wang (2002) obtained in the context of a static model.
urn:nbn:de:bsz:21-opus-69236
Keywords: F22; I30; J24; J61; O15; O40; 330; Overlapping-generations growth model; Intertemporal human capital externalities; Long-run growth effect of the prospect of migration